2019
DOI: 10.5511/plantbiotechnology.18.1119a
|View full text |Cite
|
Sign up to set email alerts
|

High frequency plant regeneration from leaf culture of <i>Neolamarckia cadamba</i>

Abstract: Neolamarckia cadamba is a miracle tree species with considerable economic potential uses as a timber wood, woody forage and traditional medicine resource. The present study aimed to establish a highly efficient and robust protocol of plant regeneration for N. cadamba. Greenish callus was induced from very young leaf explants of sterile in vitro plantlets cultured on Murashige and Skoog's (MS) medium supplemented with 3 mg l −1 thidiazuron (TDZ), 0.1 mg l −1 2,4-dichlorophenoxyacetic acid (2,4-D) and 0.05 mg l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
2
11
2
Order By: Relevance
“…The study demonstrates, for the first time, an improved, reproducible and highly efficient buds/shoots regeneration protocol of N. cadamba was developed in both cotyledonary petiole and hypocotyl explants, used the cytokinin TDZ via an intermediate callus formation. Obviously, in terms of proliferation multiple and potential genetic transformation ability, this in vitro regeneration strategy is superior to our previous research 20 . In addition, this is the first report of genetically sustainable proliferation via cotyledonary petiole and hypocotyl explants in N. cadamba.…”
Section: Resultsmentioning
confidence: 74%
“…The study demonstrates, for the first time, an improved, reproducible and highly efficient buds/shoots regeneration protocol of N. cadamba was developed in both cotyledonary petiole and hypocotyl explants, used the cytokinin TDZ via an intermediate callus formation. Obviously, in terms of proliferation multiple and potential genetic transformation ability, this in vitro regeneration strategy is superior to our previous research 20 . In addition, this is the first report of genetically sustainable proliferation via cotyledonary petiole and hypocotyl explants in N. cadamba.…”
Section: Resultsmentioning
confidence: 74%
“…Morphological examination revealed that the application of NAA produced EC specifically, which was characterized by a compact shape, pale green color, and the presence of small, granular structures. In general, EC may proceed down several morphogenic processes: somatic embryogenesis, nodular embryogenic structures (NESs), or shoot organogenesis [ 34 ]. The regeneration of shoots from leaf explants generally occurs through the induction of EC, and often requires the presence of both auxins and cytokinins [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…0.1%) of bioactive 3dihydrocadambine and cadambine in the bark and leaves. Given that we have established a highly efficient regeneration system of N. cadamba (Li et al, 2019), the genomic information presented here will greatly facilitate the elucidation of the cadambine synthetic pathway and the development of tools for enhancing bioactive productivity by metabolic engineering in microbes or by molecular breeding in plants.…”
Section: Discussionmentioning
confidence: 99%